Literature review of an adequate cuff pressure range for the management of adult patients with an artificial airway - Rosales Lillo, Felipe Gonzalo (Revista de Investigación en Logopedia, 2019)
There are different international recommendations in relation to the use of cuff pressure ranges for the management of adult patients with an artificial airway. In Chile there are no clinical guidelines on this topic. Due to this, some institutions have created their own protocols, in which different cuff pressures are recommended. The goal of this research is to find a safe pressure range to insufflate the cuff of tracheostomy tubes and endotracheal tubes. A literature review was performed with a qualitative approach of: full access articles published in English and their primary references, experimental and observational research, human population over 18 years or animals, cuff pressure recommendations and medical-scientific procedures were included. Cuff pressure range recommendations vary according to the animals studied. In human population, the ranges recommended are also different. Some current literature relating to cuff pressure values to use in patients have been based upon research performed on animals. Due to this, cuff pressure range recommendations should be based on research carried out on humans. Considering exclusively human studies with scientific statistical results, the minimum pressure to avoid the risk of aspiration is 20 cm H2O, whilst the maximum pressure to avoid the risk of tracheal damage is 30 cm H2O. New research, with recent technology used exclusively on human population, is required. The protocols used by Chilean institutions need to be revised.